High throughput development of TCR-mimic antibody that targets survivin-2B80-88/HLA-A*A24 and its application in a bispecific T-cell engager - Nobuyuki Kurosawa (Nature Portfolio, 2019)
Abstract Intracellular tumor-associated antigens are targeted by antibodies known as T-cell receptor mimic antibodies (TCRm-Abs), which recognize T-cell epitopes with better stabilities and higher affinities than T-cell receptors. However, TCRm-Abs have been proven difficult to produce using conventional techniques. Here, we developed TCRm-Abs that recognize the survivin-2B-derived nonamer peptide, AYACNTSTL (SV2B80-88), presented on HLA-A*24 (SV2B80-88/HLA-A*24) from immunized mice by using a fluorescence-activated cell sorting-based antigen-specific plasma cells isolation method combined with a high-throughput single-cell-based immunoglobulin-gene-cloning technology. This approach yielded a remarkable efficiency in generating candidate antibody clones that recognize SV2B80-88/HLA-A*24. The screening of the antibody clones for their affinity and ability to bind key amino-acid residues within the target peptide revealed that one clone, #21-3, specifically recognized SV2B80-88/HLA-A*24 on T2 cells. The specificity of #21-3 was further established through survivin-2B-positive tumor cell lines that exogenously or endogenously express HLA-A*24. A bispecific T-cell engager comprised of #21-3 and anti-CD3 showed specific cytotoxicity towards cells bearing SV2B80-88/HLA-A*24 by recruiting and activating T-cells in vitro. The efficient development of TCRm-Ab overcomes the limitations that hamper antibody-based immunotherapeutic approaches and enables the targeting of intracellular tumor-associated antigens.